Effect of coke breeze content on sintering mechanism and metallurgical properties of high-chromium vanadium-titanium magnetite. (8th August 2020) - Zhang, Liheng; Yang, Songtao; Tang, Weidong; Yang, He; Xue, Xiangxin
ABSTRACT: The coke ratio has an important effect on the behaviour of high-chromium vanadium–titanium magnetite (HCVTM) sintering. The effect of coke breeze content on sintering properties and mechanism of HCVTM was investigated in an experimental-scale sintering pot. And the softening-melting test was carried out to study the metallurgical properties of sinter. The results showed that with increasing coke breeze content from 4.0% to 6.0%, the mineral phase grains of HCVTM sinter refined. Further, the mineral content of FeO, silicate, perovskite, and magnetite increased while calcium ferrite and haematite decreased. The vertical sintering speed (VSS), tumble index (TI), productivity, and reduction disintegration index (RDI) increased while yield and reducibility index (RI) of HCVTM sinter decreased, and the softening-melting behaviour of HCVTM sinter improved with the increasing of coke breeze content.